COMPOSITION INTERRELATIONS OF PROBIOTIC STRAINS B. SUBTILIS AND PREBIOTICS FOR THE SINBIOTIC DRUG - М. А. Хархота; А. И. Осадчая; Л. В. Авдеева (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2012)
Activity of various compositions of probiotic strains B. subtilis УКМ- 5139 and B. subtilis УКМ-5140, and also lactitol and lactulosa in relation to conditionally pathogenic microorganisms is studied. It is established that the most expressed antimicrobical effect was shown by the composition consisting the cultures of the investigated strains of bacilli in the ratio 1:1. The addition of prebiotics substances to cultivation medium in concentration of 15% strengthened antagonistic activity of bacilli of conditionally pathogenic microorganisms. The level of inhibition of their growth in addition to cultivation medium of lactitol was higher in comparison with addition of lactuloses.